Pengaruh Persepsi Harga, Citra Merek dan Promosi Terhadap Keputusan Pembelian Produk Belikopi di Merr Pandugo Surabaya - Yayang Pitino; Nanis Susanti (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to explore the influence of price perception, brand image, and promotion on purchasing decisions for Belikopi products at Merr Pandugo Surabaya. Methodology/approach: The method used in this research is a quantitative research design paradigm with an emphasis on testing research variables using an approach through surveys of respondents who have experienced Belikopi products. Data were analyzed using multiple linear regression techniques and Determination Coefficient Analysis (R2) using the statistical software product version 25, involving 85 respondents who answered the questionnaires on a Likert scale. Results/findings: In testing the validity of variable dimensions involving 17 items, consisting of price perception, brand image, and promotion variables, on purchasing decisions, the results were proven to be valid because the Rcount value was greater than Rtable. In the simultaneous test or F test, the calculated F value is 51.894 > 2.72, with a significance value of 0.000 < 0.05; therefore, Ha is accepted and Ho is rejected. Thus, it can be concluded that together price perception, brand image and promotion have a significant influence on purchasing decisions. Limitations: This research only focused on Merr Pandugo Surabaya, and the findings may not be generalizable to other locations or contexts. In addition, external factors, such as economic conditions and cultural influences, have not been explored in depth and may influence consumer behavior. Contribution: This study contributes to the existing literature on consumer behavior and marketing by providing a detailed analysis of the factors that influence purchasing decisions for belikopi products in certain locations.